ChIP provides 10-fold microbial DNA enrichment from tissue while minimizing bias - Shrikant Bhute; Jon G. Sanders; Se Jin Song; Sydney Lavoie; Austin Swafford; Caitlin Guccione; Lucas Patel; Antonio Gonzalez; Michelle G. Rooks; Rob Knight; Andrew Bartko (Molecular Biology Reports, 2025)
Background Host DNA depletion is a critical tool for accessing the microbiomes of samples that have a small amount of microbial DNA contained in a high host background. Of critical practical importance is the ability to identify microbial DNA sequences in frozen tissue specimens. Here, we compare four existing commercial methods and two newly introduced methods involving chromatin immunoprecipitation (ChIP) on frozen human and pig intestinal biopsies. Results We find that all methods that rely on differential lysis of host and microbial cells introduce substantial biases as assessed by 16 S rRNA gene amplicon profiling. However, ChIP enables 10-fold enrichment of microbial DNA while introducing less bias, sufficient to make assessment possible against background, in both pigs and humans. Conclusions We recommend ChIP in situations where host depletion is important but where minimizing taxonomic bias is essential, and the MolYsis or Zymo kit for situations where host depletion level is more important than taxonomic bias. Conclusions We recommend ChIP in situations where host depletion is important but where minimizing taxonomic bias is essential, and the MolYsis or Zymo kit for situations where host depletion level is more important than taxonomic bias.